Improvement the efficacy of Al/CuPc/n-Si/Al Schottky diode based on strong light absorption and high photocarriers response - Elsayed Elgazzar (Materials Research Express, 2020)
Copper phthalocyanine has been prepared by simple chemical approach and its structural and optical properties were investigated. X-ray diffraction pattern exhibits a notable peak at $2θ =6.75^° $ assigned to the $α -\,$ phase of CuPc. SEM images show the particles distributed in nanospheres with average size at about 50 nm. The linear optical constants like optical band gap $(E_{g})$ and dielectric constants ( $ε ^{′} ,ε ^{′′} $ ) were estimated from transmittance and reflectance spectra in the wavelength range from 250 to 900 nm. The energy gap was found to be 1.62 and 2.90 eV dependent on the incident photon energy. Al/CuPc/n-Si/Al Schottky diode has been fabricated using thermal evaporation technique. The electronic parameters such as the ideality factor $(n),$ series resistance $(R_{s}),$ and barrier height ( ${φ }_{b}$ ) were evaluated in dark by applying the ( I – V ), Cheung-Chung, and Norde models. At various illumination intensities, the photocurrent sensitivity was studied based on the response of trapped charge carriers. At 1 Mhz, the built-in voltage $(V_{bi})$ and donor concentration $(N_{d})$ were calculated from ( C – V ) measurements. The findings revealed that CuPc/n-type Si can be used as photodiode in optoelectronic applications.